Maternal Age at Marriage and Risk of Childhood Stunting: Evidence from a Case-Control Study in North Sumatra, Indonesia - Sidabutar, Anjas Domini; Pratama, Irza Haicha; Fadillah, Qori; Angwyn, Wilbert; Rimadeni, Yeni; Anggriani, Theresia (Poltekkes Kemenkes Surabaya, 2025)
Stunting remains a major public health issue in Indonesia, particularly in urban areas such as Medan. While socioeconomic and nutritional factors are well recognized, the influence of maternal age at marriage on child growth is less explored. This study examined the association between maternal age at marriage and childhood stunting in Medan, Indonesia. Methods. An analytical observational study with a case–control design was conducted from January to March 2025 across several community health centres in Medan. A total of 124 mother–child pairs (62 stunted and 62 non-stunted children) were selected using cluster random sampling. Data were collected through structured interviews and health-record reviews. Stunting was defined as height-for-age Z-score < -2 SD based on WHO standards. Logistic regression was used to assess the relationship between maternal age at marriage (<25 years vs ≥25 years) and stunting, adjusting for maternal education, maternal health during pregnancy, socioeconomic status, and birth weight. Children of mothers who married before age 25 had significantly higher odds of being stunted compared with those whose mothers married later (adjusted OR = 2.85; 95% CI: 1.71-4.76; p < 0.001). Low maternal education (adjusted OR = 2.12; p = 0.021) and low birth weight (adjusted OR = 2.43; p = 0.030) were also independent predictors of stunting. Conclusion. Maternal marriage before 25 years is a strong determinant of childhood stunting in urban Medan. Delaying maternal marriage, enhancing women’s education, and strengthening maternal health programs could substantially reduce stunting prevalence. This study contributes new evidence to Indonesia’s national efforts to prevent stunting through life-course and policy-oriented interventions.